The effect of coach and player injury knowledge, attitudes and beliefs on adherence to the FIFA 11+ programme in female youth soccer - McKay, C. D.; Steffen, K.; Romiti, M.; Finch, C. F.; Emery, C. A. (British Journal of Sports Medicine, 2014)
Background: Injury knowledge and beliefs influence uptake of prevention programmes, but the relationship between knowledge, beliefs and adherence remains unclear.